Parasite-antigen driven expansion of IL-5(-) and IL-5(+) Th2 human subpopulations in lymphatic filariasis and their differential dependence on IL-10 and TGFβ. - Rajamanickam Anuradha (Public Library of Science (PLoS), 2014)
Background Two different Th2 subsets have been defined recently on the basis of IL-5 expression - an IL-5(+)Th2 subset and an IL-5(-)Th2 subset in the setting of allergy. However, the role of these newly described CD4(+) T cells subpopulations has not been explored in other contexts. Methods To study the role of the Th2 subpopulation in a chronic, tissue invasive parasitic infection (lymphatic filariasis), we examined the frequency of IL-5(+)IL-4(+)IL-13(+) CD4(+) T cells and IL-5(-)IL-4 IL-13(+) CD4(+) T cells in asymptomatic, infected individuals (INF) and compared them to frequencies (Fo) in filarial-uninfected (UN) individuals and to those with filarial lymphedema (CP). Results INF individuals exhibited a significant increase in the spontaneously expressed and antigen-induced Fo of both Th2 subpopulations compared to the UN and CP. Interestingly, there was a positive correlation between the Fo of IL-5(+)Th2 cells and the absolute eosinophil and neutrophil counts; in addition there was a positive correlation between the frequency of the CD4(+)IL-5(-)Th2 subpopulation and the levels of parasite antigen - specific IgE and IgG4 in INF individuals. Moreover, blockade of IL-10 and/or TGFβ demonstrated that each of these 2 regulatory cytokines exert opposite effects on the different Th2 subsets. Finally, in those INF individuals cured of infection by anti-filarial therapy, there was a significantly decreased Fo of both Th2 subsets. Conclusions Our findings suggest that both IL-5(+) and IL-5(-)Th2 cells play an important role in the regulation of immune responses in filarial infection and that these two Th2 subpopulations may be regulated by different cytokine-receptor mediated processes.